(untitled) (Research, Society and Development, 2025)
Childhood is a period of vulnerability, where the child may be susceptible to experiencing traumas, such as child sexual abuse, causing various psychological problems. Thus, this study aimed to: identify in the scientific literature the association of sexual abuse in childhood and the development of borderline personality disorder and understand the role of nurses in the context of sexually abused children. This is an integrative literature review carried out via the Virtual Health Library, in the databases: Medical Literature Analysis and Retrieval System Online, Nursing Database, Latin American and Caribbean Literature in Health Sciences, using the descriptors combined with the Boolean operator AND, in Portuguese, English and Spanish, during the months of October and November. Articles published between 2013 and 2022, available online, were included. Sexual abuse is a serious risk factor in the development of BPD, especially in women. Rates of sexual abuse are significantly higher in patients with BPD compared to other abuses. Furthermore, patients with this association have a greater number of suicide attempts and serious events such as non-suicidal self-injury, smoking, alcohol use, sexual impulsivity, longer time and number of psychiatric hospitalizations. It has been shown that childhood trauma influences neurodevelopment and brain structure in patients later diagnosed with BPD. It is believed that nursing, accompanied by a multidisciplinary team, needs to be able to receive and understand the child victim of sexual abuse, seeking care strategies to prevent future harm.